As rebeliões de junho de 2013, para as centrais sindicais da classe trabalhadora brasileira - Vieira, Luís Augusto (2021)
This thesis aims to: analyze June 2013 Rebellions for the Brazilian working class union organizations. To this end, we list three union centers as researched entities: Central Única dos Trabalhadores (CUT), Força Sindical and CSP-Conlutas. The reasons that led to the research concern the researcher's field of studies and research; his militant participation in these spaces; the fact that these are the largest mass manifestation in Brazil, in historical and recent periods (BRAGA, 2017); because they lack analyzes that privilege the class character of such rebellions and because their repercussions are poorly elucidated, especially that of union organizations. The hypothesis suggested was that, despite important studies about June 2013, there was a gap regarding interpretations and meanings for Brazilian working class organizations (which proved to be correct). To this end, we make use of historical-dialectical materialism founded on the Marxist tradition, with its method of investigation, analysis and exposition, as we understand that this is the research method that stands out as the most appropriate for the object in question (MARX, 1983; 2013). And as methodological procedures, we resort to a treatment with a qualitative approach, as we understand that the experimental-mathematical analysis, as suggested by quantitative research, is not the most adequate to the researched theme (SEVERINO, 2007). From the results obtained, it appears that, in general, the significance of the June Rebellions is similar in the readings of the CUT and Força Sindical and presents differences regarding the CSP-Conlutas. When it comes to more detailed questions, the differences between the three centrals are more evident